The Effect of Postponement Strategy Towards the Financial Performance of Manufacturing Companies in Malaysia - Ramasamy, Sethuraman; Husin, Nor Azilah; Jamaluddin, Zaharuzaman (Archives of Business Research, 2023)
Today’s manufacturing companies must simultaneously deal with externally increasing customers multi-item requirements with rapid lead-time, demanded high-quality products, but internally on a limited capacity. This study aims is to explore the important elements in postponement strategies and to identify the impact of postponement strategies towards financial performance of the manufacturing companies in Malaysia. Using qualitative research method, this study employs standardized open-ended interviews with five key informants from electronic manufacturing services, solar panel, telco, medical, and latex industries. ATLAS.TI was used to analysed the data. This study reveals that postponement strategies implemented have saved various costs, enhance its product quality, increase production speed, and definitely enhance their profits which results from increase revenue. Overall, this study supports the Service Level Model which suggest that by integrating demand management processes in the postponement strategies, the service level offered to customers can be achieved and it leads to the improvement on the yearly financial performance. The empirical evidence of this study provides a solid foundation for the manufacturing companies in Malaysia to incorporate postponement strategies while observing the market strategy to grab more customers for business enhancement.